Determinant factors of obesity in urban and rural studies on adolescents in Banten Province, Indonesia - Perdanawati, Mia; Nugraheni, Sri Achadi; Syauqy, Ahmad; Noer, Etika Ratna; Muniroh, Muflihatul (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: The prevalence of obesity which continues to grow in children and adolescents is a concern since it increases degenerative disease risk. Obesity is not only a problem in urban areas, but it is also growing in rural areas.Objective: The aim of this study was to analyze the determinants of obesity in adolescents in rural and urban areas in Banten Province.Materials and Methods: This research design used a case-control method with a purposive sampling technique. The sample in the study consisted of 160 adolescent subjects from 2 different schools. Each school representing 40 case samples that were adolescents with obesity and control adolescents with a normal body mass index. This study was conducted at one school in Cilegon City to represent the urban sample and one school in Pandeglang Regency to represent the rural sample. For each sample, body weight and height were measured, filling out the SQ-FFQ, International Physical Activity Questioner (IPAQ), Pittsburgh Sleep Quality Index and DASS-42 (Depression Anxiety Stress Scale) questionnaires. Data regarding the results of air quality monitoring which includes data (PM10, SO2 O3 and NO2) was obtained from the Environmental Service. Meanwhile, data were analyzed by using Chi-Square and logistic regression.Results: The determinants of obesity in adolescents in rural were protein intake more than RDA (p=0.003 OR=9.948), low physical activity (P=0.005 OR=22.094), high of  SO2 exposure (P=0.005 OR=19.817) and bad sleep quality (P=0.007 OR=8.901) while adolescents in urban were protein intake more than RDA  (p=0.001 OR=21.570), bad sleep quality (p=0.002 OR=16.550), high stress level (p=0.006 OR=15.922) and carbohydrate intake more than RDA  (p=0.072 OR=5.044).Conclusion: Protein intake is the biggest determinant of the incidence of obesity in adolescents both in rural and urban areas.